The protective role of Zingerone in a murine asthma model via activation of the AMPK/Nrf2/HO-1 pathway. Issue 7 (16th March 2021) - Zhu, Yingjie; Wang, Chunyan; Luo, Jingjing; Hua, Shucheng; Li, Dan; Peng, Liping; Liu, Hongmei; Song, Lei
Abstract : Zingerone possesses the potential to relieve asthma via upregulating the AMPK/Nrf2/HO-1 signaling pathway. Abstract : Asthma is one of the most common illnesses associated with chronic airway inflammation; however, there are currently no effective therapies apart from glucocorticoids. Zingerone (ZIN), an active compound isolated from ginger, has been reported to have a broad spectrum of pharmacological properties. In this study, Zingerone was administrated to H2 O2 -stimulated mouse airway epithelial cell line MLE12 cells and asthmatic mice. The concentration of cytokines was evaluated using enzyme-linked immunosorbent assay (ELISA). Hematoxylin–eosin (HE), Periodic Acid-Schiff (PAS) and Masson staining were used for histological analyses. Protein levels in cells or lung tissues were determined using western blot, immunohistochemistry staining. The results showed that treatment with Zingerone dramatically inhibited oxidative stress and the inflammatory response in MLE12 cells stimulated with H2 O2 and asthmatic mice. Furthermore, Zingerone treatment could decrease the expression of phosphorylated (p)-IκBα and p65 (nuclear) and increase the expression of phosphorylation of AMP-activated protein kinase (p-AMPK), nuclear factor erythroid-2-related factor 2 (Nrf2), and hemeoxygenase-1 (HO-1) to alleviate oxidative damage and inflammation both in vivo and in vitro . In addition, Zingerone treatment reduced the exudation and infiltration of inflammatory cells and suppressed goblet cell hyperplasia in a murine asthma model. Treatment with Zingerone also decreased the level of interleukin (IL)-4, IL-5, IL-13, and increased the level of interferon gamma (IFN-γ) in the BALF and attenuated airway hyperresponsiveness (AHR). However, inhibition of AMPK or Nrf2 suppressed the cellular protective, antioxidative, and anti-inflammatory properties of Zingerone. Taken together, these results demonstrate that Zingerone possesses the potential to relieve asthma via upregulating the AMPK/Nrf2/HO-1 signaling pathway.